System Dynamic modelling approach for resolving the thermo- chemistry of wood gasification - Boiger, G (The International Journal of Multiphysics, 2015)
For Multiphysics problems that require a thorough understanding of multiple, influential, highly transient process parameters, a System Dynamic model can constitute either an alternative option, or a compact prelude to a more expensive 3-D Finite Element or Finite Volume model. As a rather uncommon example for the application of such a modelling method, this work presents a System Dynamic modelling concept, devised for resolving the thermo-chemistry within a wood gasification reactor. It compares the modelling concept as well as its results to a classic, thermo-chemical solution algorithm based on the minimization of LaGrangian Multipliers for resolving the gasification equilibrium equations. In contrast to the latter, the System Dynamic solver can consider the impact of reaction kinetics as well as molecular mass transfer effects on the gasification equilibrium. Thus the transient production rates of methane, hydrogen, carbon (di-) oxide and water, as well as the residual amounts of pyrolysis gas and oxygen, which occur during the gasification of a wood particle, can be predicted.